SÍNTESE, CARACTERIZAÇÃO ESTRUTURAL E BIOINORGÂNICA DE NOVOS COMPLEXOS DE COBRE(II) COM LIGANTES BASEADOS EM NÚCLEOS PIRAZOLÍNICOS SUBSTITUÍDOS - Kátia Veronica Tenorio (2023)
This work consists of a study related to the synthesis, structural characterization, study of the cytotoxic activity and interaction with DNA and HSA of two new Copper(II) complexes with 1,3,5-trisubstituted pyrazolines as ligands. The complexes were obtained from the CuCl2·2H2O salt with 1,3,5-trisubstituted pyrazolinic linker in the ratio (1:1) in a mixture of EtOH/CH2Cl2/CH3CN solvents. The complexes were obtained in the form of green crystals, which can be represented simply in the general formula [Cu(L)Cl]·nH2O. For the characterization, single-crystal X-ray diffraction techniques were used, which demonstrated that the pyrazoline ligand is coordinated in a tridented way by atoms of N and one of O and completing the sphere of coordination to the metal by a Cl atom, forming a slightly distorted quadratic geometry, paramagnetic electron resonance spectroscopy corroborated the geometry of the complexes and we could also observe that the analysis in frozen DMSO does not occur the coordination of DMSO in the complexes. Molecular orbital calculations were performed using the Time-Dependent Functional Density Theory (TD-DFT) method to assist in the interpretation of electronic transitions observed in UV-Vis molecular absorption spectroscopy, mixed electronic transitions of the MLCT type were observed. (metal to ligand transition), LMCT (ligand to metal transition) and IL (intraligant). The cytotoxic activity of the synthesized complexes was evaluated, a superior action of the complexes was observed when compared to free ligands for tests performed in vitro. The interaction of the complexes and ligands with DNA and HSA was also evaluated and it was observed that there is a weak to moderate interaction, both for free ligands and for the complexes, in addition to presenting high binding constants (Kb), which were in the order of 103 for the complexes and 102 for the ligands, and they occur spontaneously, since it was verified that the variation of the Gibbs free energy was negative (ΔG < 0). By fluorescence spectroscopy, the Stern-Volmer constant (Ksv) was used to determine the interactive capacity of the compounds. The determined Ksv values were: in the order of 103 for the complexes and ligands for the interaction with DNA and for the complexes in the interaction with HSA, since the ligands with HSA were in the order of 101. Also, with the help of theoretical studies by Molecular docking, it was possible to estimate the preferential position of the compounds when interacting with DNA that indicated the minor groove as the preferential site of the and that the main interaction is by van der Waals forces. For HSA, the interaction occurs preferentially through site III and the main type of interaction is through van der Waals forces.